ASUPAN ENERGI DENGAN KEJADIAN UNDERWEIGHT PADA ANAK USIA 6 – 59 BULAN DI KOTA DEPOK - Anggraeni, Welly; Sudiarti, Trini (Poltekkes Kemenkes Bandung, 2023)
Underweight in children is still remains the public health problems in the world. The prevalence of underweight children under five in Depok City in 2022 is 12.1 percent. This study aimed to analyze energy intake and other factors with the incidence of underweight in children aged 6 - 59 months old in Depok City. This study a used cross-sectional study design. This study used secondary data from Grant research of indexed publication Q2 TA 2022/202 Batch 3 Kemenristek. The samples were 311 with the criteria of children aged 6 – 59 months old with complete data and non-extreme data. Chi-square test was used to determine the relationship between sex, low birth weight, deworming, complete immunization, ARI, diarrhea, energy intake, protein intake, fat intake, carbohydrate intake and family income and underweight. A multivariate binary logistic regression was employed to determine the factors that contribute to the incidence of underweight in children aged 6 - 59 months old. The results of multivariabel logistic regression analysis showed energy intake as the dominant factor in the incidence of underweight in children aged 6 - 59 months old (p-value 0.001). Children with insufficient energy intake are 10.06 times more likely to be underweight than children with sufficient energy intake.